Estudo imuno-histoquímico da co-expressão de citoqueratinas, vimentina e actina em neoplasias de glândula salivar - Carvalho, Yasmin Rodarte [UNESP] (1998)
Human salivary gland tumors originated from intercalated ducts present a broad range of histologic and cytologic patterns, mainly due to the presence of myoepithelial cells. The aim of this study is to verify the differentiation grade of neoplastic cells and a possible relation between myoepithelial cell differentiation and the presence of luminal secretory contents. The expression of vimentin and cytokeratin (CK) intermediate filaments, actin myofilament and epithelial membrane antigen (EMA) was investigated by double labeling immunocytochemical technique, in thirty salivary gland neoplasms: 5 pleomorphic adenomas, 5 myoepitheliomas, 3 basal cell adenomas, 7 adenoid cystic carcinomas (ACC) and 10 polimorphous low grade adenocarcinomas (PLGA). Tumors with intercalated duct differentiation (pleomorphic adenomas, basal cell adenomas and ACC) express CKs 7, 8, 18 and 19 in the luminal cells and coexpress eventually CK14 with these CKs. Some luminal cells stained with anti-EMA antibody, mainly where a secretory content in the lumen was observed. Outer ductal cells and other myoepithelial-like cells express vimentin, sometimes coexpressing actin and/or CK14 with vimentin. Plasmacytoid cells in myoepitheliomas and pleomorphic adenomas express vimentin and rarely CKs 7, 8, 18 and 19, sometimes coexpressing these CKs with CK14 but they are negative for the remaining antigens. Tumors without intercalated duct differentiation (solid basal cell adenoma and PLGA) express vimentin and CKs 7, 8, 14 and 18, sometimes coexpressing CKs 8 and 18 with CK14. In conclusion, in tumors with intercalated duct differentiation, myoepithelial cells express vimentin and sometimes coexpress actin and/or CK14 with vimentin, never coexpressing other CKs with vimentin. CK14 and actin are independently expressed by myoepithelial cells, so their expression is probably induced by different stimulus. However, the secretory function of luminal cells, visualized by EMA staining, ....